Intervention to Improve Timing of Preoperative Antibiotic Prophylaxis in Major Elective Surgery - Shah, Jay N; Maharjan, SB; Manandhar, K; Shrestha, A; Piya, R; Basnet, NB (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: Timely administration of antibiotic before incision ensures effective concentration in blood and tissues. Compliance with established guidelines is problematic due to logistics. Aim of this study was to improve timing of antibiotic prophylaxis (AP) with appropriate intervention in existing practices. Methods: Cross sectional study was conducted from May-June 2011 with target of enrolling at least 100 elective major cases (excluding obstetrics) who received AP before surgery. Anesthetists took responsibility of AP administration (Cefazoline 1 g as per our protocol unless indicated otherwise) instead of floor nurse as our earlier practice. Institutional ethical committee approved the study. Data collected in a pre-designed proforma was analyzed using Microsoft Excel. Results: Out of 120 patients, 64% were female. Average age was 43 years (4 to 87). General surgery cases were 51%, urosurgery 20%, gynecology and orthopaedic each 13% and others 6%. One hundred nineteen (99%) received AP before incision, 58(48%) within 60 to 30 minutes before incision and 1 (1%) after the incision. Conclusions: Anesthetist taking charge of the team for AP administration is a feasible option to improve compliance. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 15-18 DOI: http://dx.doi.org/10.3126/njog.v7i1.8827